The mutual study of the Ugandan and Rostov rice varieties - P. I. Kostylev; E. V. Krasnova; A. V. Aksenov; J. Lamo (Зерновое хозяйство России)
Rice is one of the most important food crops in the world. The development of new rice varieties requires a thorough study and involvement of gene pool from different countries in breeding work. The purpose of the current study was to conduct a mutual ecological testing of the rice varieties in the Rostov region of Russia (FSBSI “Agricultural Research Center “Donskoy”) such as ‘Akustik’, ‘Aromatik 1’, ‘Aromatny’, ‘Kuboyar’, ‘Yuzhanin’ and the Ugandan (NaCRRI) ‘Nerica 1’, ‘Nerica 4’, ‘Komboka’, ‘Wita 9’. These samples have shown a wide range of resistance to blast and other diseases. The research was carried out in the Proletarsky district of the Rostov region. As a result, the rice varieties were studied for a number of important economic and biological traits. The growing season from sowing to ripening was 131–139 days for two varieties ‘Nerica 1’ and ‘Nerica 4’ under the conditions of the Rostov region, and 110 days for the standard variety ‘Komandor’. The other two varieties ‘Komboka’ and ‘Wita 9’ were very late maturing and did not bloom. All samples had a modern low-growing plant habit with upright rigid leaves and long drooping panicles (17–23 cm). Plant height of the Ugandan varieties ranged from 70 to 90 cm. The grains were elongated with 29–31 mg of weight. Number of spikelets per panicle was 85 and 200, respectively. The varieties ‘Nerica 1’ and ‘Nerica 4’ were used in hybridization with the Russian varieties ‘Kontakt’ and ‘Boyarin’. The preliminary study of Russian rice varieties in Uganda showed that RU 105 (‘Aromatny’) and RU 101 (‘Aromatik 1’) were resistant to rice yellow spot virus (‘RYMV’), blast and brown leaf spot. The varieties were selected for further study in the conditions of Uganda.